Modern extraction techniques optimized to extract betacyanins from Gomphrena globosa L. - Roriz, Custódio Lobo (2018)
Gomphrena globosa L. is a source of betacyanins, molecules with high colorant power. In order to replace conventional extraction techniques, microwave (MAE) and ultrasound assisted extraction (UAE) processes were optimized by the response surface methodology (RSM) to maximize the recovery of betacyanins from G. globosa. A five-level full factorial design of 24 combinations and 4 replicates was implemented for MAE and UAE. The optimum processing conditions for MAE (t = 8 min; T = 60 °C; Et = 0%; and S/L = 5 g/L) conducted to an extraction yield of 39.6 ± 1.8 mg/g dry weight, while for UAE (t = 22 min; P = 500%; Et = 0%; and S/L = 5 g/L) a value of 46.9 ± 4.8 mg/g was achieved, validating the UAE more suitable to obtain the target compounds. This technique can provide extracts rich in betacyanins and with high potential to be used as natural colorants.